Surveillance for an Emerging Disease: Dengue Hemorraghic Fever in Puerto Rico, 1988-1997 - Rigau-Pérez, José G.; Association of Epidemiologists, The Puerto Rico (Puerto Rico Health Sciences Journal, 2014)
see manuscript